The present-day state of tectonic stress in the offshore Kutch-Saurashtra Basin, India. (April 2019) - Sen, Souvik; Kundan, Ashani; Kalpande, Vikrant; Kumar, Mithilesh
Highlights: Stress magnitudes and orientations have been estimated from high resolution geophysical logs from offshore Kutch-Saurashtra basin. Pore pressure (PP) interpreted as hydrostatic, calibrated with extensively available direct downhole pressure measurements. Shmin, SHMax have been interpreted and calibrated with Leak Off Tests (LOT) and Extended Leak Off Tests (XLOT). SHMax > Sv > Shmin suggests a Strike Slip fault regime in Kutch-Saurashtra area (Sv = vertical stress). Wellbore Breakouts of A-C quality and Shear wave anisotropy analyses confirms a NNE orientation of SHMax (N10°E to N20°E), which is in good agreement with the World Stress Map data. Abstract: Exploration activity in the Kutch-Saurashtra area has drawn major attention and because of the recent hydrocarbon discoveries offshore Kutch-Saurashtra basin is now moved from category III to II. Accurate understanding of the full present-day stress tensor and pore pressure is critical for field development. In this study, pore pressure, stress magnitudes and horizontal stress direction have been estimated from high resolution geophysical logs and various direct downhole measurements recorded in the studied offshore exploratory wells. Extensive availability of subsurface pressure measurements confirms hydrostatic pore pressure in the tertiary sediments. Magnitudes of vertical, minimum and maximum horizontal stresses indicate a strike slip tectonic stress regime. Wellbore breakouts of A-C qualities have been identified in density image logs and four arm caliper logs, indicating a NNE trend (N10°E to N20°E) of SHMax (maximum horizontal stress). The same has been confirmed from Shear wave anisotropy analysis as well. The interpreted stress direction is in good agreement with the World Stress map data available from the adjacent area. This study is significant in understanding the subsurface behavior during drilling, reservoir modeling, future well stimulation and production optimization.